2014
DOI: 10.4018/ijhcitp.2014010104
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Change

Abstract: The skill shortage is becoming an ever-increasing challenge for Information Technology (IT) departments. To allocate the resources in the best possible way is even more important. The challenge is to improve the company not only on the side of the organizational and process level, but to develop new strategies and approaches in human resource management. Only a symbiosis of these disciplines will enable relevant and indispensable employees to promote loyalty to the company. A frequent change of the work place,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In addition human resources management is a very complex domain on its own and a SLR conducted in March 2014 has shown that the the problem of skill shortage in companies can only be solved if further scientific areas, e.g. psychology, sociology or organization theory are considered as well (Radant, 2014;Radant, Colomo-Palacios, & Stantchev, 2014). This paper shows that the research community currently does not provide satisfactory answers for the problem of scarcity of talent and skill shortage in IT-departments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition human resources management is a very complex domain on its own and a SLR conducted in March 2014 has shown that the the problem of skill shortage in companies can only be solved if further scientific areas, e.g. psychology, sociology or organization theory are considered as well (Radant, 2014;Radant, Colomo-Palacios, & Stantchev, 2014). This paper shows that the research community currently does not provide satisfactory answers for the problem of scarcity of talent and skill shortage in IT-departments.…”
Section: Discussionmentioning
confidence: 93%
“…Colomo-Palacios, Casado-Lumbreras, Soto-Acosta, Misra, & García-Peñalvo, 2012). Thus, in a perspective of demographic change skilled software practitioners will continue to be hard to find due to decreasing birth rate (Radant, 2014). While systematic resource governance approaches (Stantchev, Petruch, & Tamm, 2013) and project portfolio management paradigms Stantchev, Franke, & Discher, 2009) can provide higher utilization of available human resources, this provides only a limited amelioration of the resource problem in the field.…”
Section: Introductionmentioning
confidence: 99%